The polypharmacy of the third age in Greece - Theodosopoulou, Eleni; Tzavelas, George; Raftopoulos, Vasilios (My University, 2000)
The aim of this paper is to study the attitude of the third age towards of the use of drugs. The factors related to the excessive use of drugs are examined and the appearance of allergies is considered. The use of anti-depressant drugs is also studied in terms of sex, age, residence, education and if they live in a nursery or not.
Keywords: Antidepressants; Drugs; Polypharmacy; Pharmacology